2019
DOI: 10.1002/aenm.201901181
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Oxygen Redox for Excellent Power Capability in Layered Sodium‐Based Compounds

Abstract: resources. [1][2][3][4][5] However, because of the slightly higher standard electrode potential of sodium (−2.7 V vs the standard hydrogen electrode (SHE)) than lithium (−3.02 V vs SHE), high-capacity electrode materials are needed for SIBs to compensate for their lower operation voltage and to achieve energy densities comparable to those of LIBs. It can be assumed that the cost of SIBs can be lowered relative to that of LIBs because of the cost-effectiveness of sodium resources. [6] These factors encourage us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 50 publications
(139 reference statements)
1
54
0
Order By: Relevance
“…107 When charged up to 5 V loss of oxygen can be detected from P2-Na 0. 78 110 More recently, increasing the covalency of the TM-O bond has been shown to be effective in suppressing oxygen release, hence improving electrochemical performance. 86 The TM-O distance and TM-O bonding energy have also been identied as important factors in determining the activity and reversibility of the oxygen redox reaction.…”
Section: Anionic Redox Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…107 When charged up to 5 V loss of oxygen can be detected from P2-Na 0. 78 110 More recently, increasing the covalency of the TM-O bond has been shown to be effective in suppressing oxygen release, hence improving electrochemical performance. 86 The TM-O distance and TM-O bonding energy have also been identied as important factors in determining the activity and reversibility of the oxygen redox reaction.…”
Section: Anionic Redox Activitymentioning
confidence: 99%
“…112 Through comparison of X-ray photoelectron spectroscopy (XPS), operando Raman spectroscopy and electrochemical data, Jia et al found that compared to the sodium decient O3-Na 0. 6 110 DFT calculations suggest that the overlapping Co 3d and O 2p orbitals as well as the reduced bandgap of z 0.61 eV (cf. z 2.65 eV for the analogous Co free composition) upon incorporation of Co facilitates facile electron transfer, enabling long term oxygen redox reversibility.…”
Section: Anionic Redox Activitymentioning
confidence: 99%
“…Recently, we suggested the occurrence of an oxygen redox reaction in P2‐Na 2/3 [Mn 0.7 Zn 0.3 ]O 2 , for which the combination of O 2−/1− and Mn 4+/3+ contributed to rechargeable capacity. [ 23 ] Kim et al [ 24 ] observed the oxygen redox in P2‐Na 2/3 [Mg 0.2 Mn 0.6 Co 0.2 ]O 2 , which enabled long‐term cycling assisted by the presence of CoO bonds, facilitating electron transfer with the overlapping of orbitals between O 2− 2p and Co 3+/4+ 3d ( t 2g ). Despite these successes of the oxygen redox reaction toward contributing additional capacity in P2‐layered compounds, the main shortcoming is that the resulting operation voltage remains still low because the main redox species of Mn 4+/3+ is achieved in the voltage range of 1.5–2.7 V versus Na + /Na.…”
Section: Introductionmentioning
confidence: 99%
“…In order to meet the greatly increased energy consumption demand, the development of sodium ion batteries (SIBs) technologies with low cost, long life, and high electrochemical performance are imminent. [ 1–5 ] In the last decade, researchers have explored many cathode materials used in SIBs, [ 6–8 ] including sodium superionic conductor materials, [ 9–11 ] sodium‐based layered oxides, [ 12–15 ] fluorophosphates, [ 16–18 ] and organic materials. [ 19 ] However, the restricted space of layered oxide for sodium ions diffusing due to the close‐packed oxygen ion array connected to transition metal elements severely hinders the improvement of SIBs performance.…”
Section: Introductionmentioning
confidence: 99%